Redesain UI UX Website Lemonder Indonesia Menggunakan Metode Design Thinking Untuk Meningkatkan Media Promosi - Aditiya, Angger Mahkota; Haq, Endi Sailul; Panduardi, Farizqi; Hakim, Lutfi; Wibowo, Galih Hendra (Jurnal Informatika dan Komputer, 2024)
Lemonder Indonesia's website is designed to compete in the market for lemons, vegetables, and other high-quality fresh products. This website provides easy access to information about the company and its products for all users. The purpose of this research is to increase customer trust and improve the design of the Lemonder Indonesia website. The Design Thinking approach is used as a method for redesigning the website. This method includes five stages: Empathy, Define, Ideate, Prototype, and Testing. It focuses on consumer-centered innovation, emphasizing product and service designs that attract attention in the business world. During the testing phase, this research uses usability testing to evaluate the effectiveness of the website redesign. The System Usability Scale (SUS) involves using a questionnaire distributed via Google Forms. Before the redesign, the SUS score was 51.75%, which is a grade D with a "poor" indicator. However, after the redesign, the SUS score significantly increased to 85.08%, which is a grade A with an "excellent" indicator. This result demonstrates that the SUS testing in this research was successful and that the new design is well-received by users.